KAWUNG AND PARANG BATIK PATTERN AS PLAYER UNKNOWN'S BATTLEGROUNDS MOBILE GAME PLAYER COSTUME DESIGN ELEMENTS - Revan, Revan Arfian; Afrizal (Acintya, 2024)
A costume is a fashion design that has the aim to create a form of an imaginary character. The Kawung and Parang Batik is an original pattern from Central Java which could add to represent ideas for creating a cultural identity of a  beautiful and dignified. The creation method to make this costume design uses the method of Prof. Drs. SP Gustami, S.U. which includes three stages: the exploration stage, the design stage, and the creation stage. PUBG Mobile is a world well known battleground fighting game that not only focuses on gameplay but also emphasizes creativity in the costumes used by players. In fact, in 2020 PUBGM Creative was formed as a forum to accommodate costume designs packaged as a costume design competition which include three assessment stages: a curation stage, an assessment stage and a voting stage. A PUBG costume design combined with Kawung and Parang batik pattern could be an effort to preserve Indonesian culture to the young generation around whole world through the online game